2019
DOI: 10.1149/2.0261911jes
|View full text |Cite
|
Sign up to set email alerts
|

In Operando Analysis of Passive Film Growth on Ni-Cr and Ni-Cr-Mo Alloys in Chloride Solutions

Abstract: The instantaneous kinetics of oxide formation and growth, in competition with passive film dissolution and breakdown, were investigated for Ni-22 Cr and Ni-22 Cr-6 Mo (wt%) during single step passivation at +0.2 V SCE . Experiments were conducted in selected acidic and alkaline chloride-containing environments using simultaneous AC and DC electrochemistry; including on-line Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). In parallel experiments, in-situ neutron reflectometry (NR) and ex-situ X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 109 publications
1
37
0
Order By: Relevance
“…To evaluate the current thermodynamic analysis with an experiment, the atomic emission spectroelectrochemistry (AESEC) [49][50][51][52] was introduced to measure the total quantity of dissolved alloy components in aqueous solution, which was shown to be consistent with the 3D-APT and XPS analysis 36,37,52,53 . AESEC measurements of dissolved alloy components were performed in 0.1 M (i.e., mol per liter or molarity) NaCl, pH = 4 solution at applied potentials from 0.00 to 0.34 V vs. SHE.…”
Section: Experimental Validationmentioning
confidence: 99%
“…To evaluate the current thermodynamic analysis with an experiment, the atomic emission spectroelectrochemistry (AESEC) [49][50][51][52] was introduced to measure the total quantity of dissolved alloy components in aqueous solution, which was shown to be consistent with the 3D-APT and XPS analysis 36,37,52,53 . AESEC measurements of dissolved alloy components were performed in 0.1 M (i.e., mol per liter or molarity) NaCl, pH = 4 solution at applied potentials from 0.00 to 0.34 V vs. SHE.…”
Section: Experimental Validationmentioning
confidence: 99%
“…For steady-state corroding systems, the EIS spectrum may in some cases be used to estimate the corrosion rate without significant electrochemical perturbation, and the EIS spectrum itself is often considered a fingerprint for specific mechanisms revealing different kinetic processes over a wide range of time constants. It is straightforward to perform EIS simultaneously during an AESEC experiment and Cwalina, et al, 87 used high-frequency AC electrochemical measurements to follow the growth of oxide films for the Ni-Cr-Mo system during conventional DC experiments coupled with ICP-MS measurement of elemental dissolution rates.…”
Section: Alternating Current and Potential Techniquesmentioning
confidence: 99%
“…Oxide formation at an applied potential in the passive range was extremely rapid and efficient, with lower quasi-steady-state passive current densities than for the commercial alloy C-22. Oxide thickness at the quasi-steady-state condition was in the nanometer range and consistent with logarithmic or reverse-logarithmic growth . XPS analysis of a sample polarized at a potential in the passive region indicated that all elements in the alloy were oxidized.…”
Section: Metal Corrosionmentioning
confidence: 55%
“…Oxide thickness at the quasi-steady-state condition was in the nanometer range and consistent with logarithmic or reverselogarithmic growth. 397 XPS analysis of a sample polarized at a potential in the passive region indicated that all elements in the alloy were oxidized. Using APT, the oxide was found to be a nonstoichiometric solid solution closely resembling a highly disordered corundum structure with significant enrichment in Cr and Ru, Mo and W near their bulk composition, and depletion of Fe and Ni (Figure 28).…”
Section: Corrosion and Design Of Multiple Principal Element Alloysmentioning
confidence: 99%